2020
DOI: 10.3389/fonc.2020.565306
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblast Density, Prognostic Characteristics, and Recurrence in Head and Neck Squamous Cell Carcinoma: A Meta-Analysis

Abstract: IntroductionThe progression and clinical course of head and neck squamous cell carcinoma (HNSCC) relies on complex interactions between cancer and stromal cells in the tumor microenvironment (TME). Among the most abundant of these stromal cells are cancer-associated fibroblasts (CAFs). While their contribution to tumor progression is widely acknowledged, and various CAF-targeted treatments are under development, the relationship between CAF density and the clinicopathologic course of HNSCC has not been clearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 81 publications
1
43
0
Order By: Relevance
“…This is a consequence of fibroblast activation and enhanced deposition of ECM [ 165 ]. Indeed, an enrichment in αSMA-positive fibroblasts can be found in chemo and radiotherapy treated tumours [ 158 , 166 ] and stromal signatures are often associated with a worse outcome regarding disease free survival [ 166 , 167 , 168 , 169 ]. High amounts of ECM can then activate pro-survival pathways in cancer cells and impair the response to radiotherapy as well as to chemotherapy, in an integrin β1-dependent manner [ 87 , 88 , 170 , 171 , 172 ].…”
Section: Fibroblastsmentioning
confidence: 99%
“…This is a consequence of fibroblast activation and enhanced deposition of ECM [ 165 ]. Indeed, an enrichment in αSMA-positive fibroblasts can be found in chemo and radiotherapy treated tumours [ 158 , 166 ] and stromal signatures are often associated with a worse outcome regarding disease free survival [ 166 , 167 , 168 , 169 ]. High amounts of ECM can then activate pro-survival pathways in cancer cells and impair the response to radiotherapy as well as to chemotherapy, in an integrin β1-dependent manner [ 87 , 88 , 170 , 171 , 172 ].…”
Section: Fibroblastsmentioning
confidence: 99%
“…Cancer-associated fibroblasts (CAFs), as the major components of TME, have been extensively explored and are known to be involved in diverse cellular processes, including cell differentiation, proliferation, and stemness; extracellular matrix (ECM) remodeling; and cell migration and apoptosis, all of which can exert critical roles in tumor biological behaviors, including tumorigenesis, tumor growth, energy metabolism, tumor immunity, angiogenesis, tumor progression, recurrence, and metastasis. 9 11 The biological activities of CAFs are mediated by various intracellular and extracellular factors, especially those in signaling pathways closely related to cancer progression, which might be targeted for anticancer therapy. Since CAFs exert molecular and functional heterogeneity in different cancers and even in different stages of the same type of tumor and because of the specific crosstalk between CAFs and cancer cells, 12 any therapeutic strategies developed should exploit the specificity and diversity of CAFs to optimize treatment efficacy for targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between the tumor and the CAFs play an important role in tumor progression in several solid cancers [ 15 , 16 , 17 , 18 ]. Across multiple studies, increasing CAF density or activated oncogenic signaling pathways in CAFs are found to be associated with poor prognosis in head and neck, oral, gastric, hepatocellular, and esophageal cancers [ 15 , 16 , 17 , 18 ]. Activated CAF may enhance metastasis, directly or indirectly, by releasing growth factors and cytokines to stimulate growth and epithelial-mesenchymal transition [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between the tumor and the CAFs play an important role in tumor progression in several solid cancers [15][16][17][18]. Across multiple studies, increasing CAF density or activated oncogenic signaling pathways in CAFs are found to be associated with poor prognosis in head and neck, oral, gastric, hepatocellular, and esophageal cancers [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%